Green Hydrogen: Unleashing the Potential for Sustainable Energy Generation - M.A. Elazab; Abdelrahman T. Elgohr; Mohamed Bassyouni; Abd Elnaby Kabeel; Mohammed El Hadi Attia; Mohamed Kamel Elshaarawy; Abdelrahman Kamal Hamed; Hassan A.H. Alzahrani (Results in Engineering, 2025)
Green hydrogen is poised to play a pivotal role in the transition to a sustainable, carbon-neutral future. This study provides a comprehensive review of the production, storage, transportation, and applications of green hydrogen. Generated through electrolysis using renewable energy sources, green hydrogen is a clean, versatile energy carrier with significant potential to decarbonize key sectors such as transportation, industry, and power generation. The decreasing costs of renewable energy, particularly solar and wind, coupled with advancements in electrolysis technologies, have enhanced the economic viability of green hydrogen production. However, challenges persist, including improving efficiency, reducing costs, scaling infrastructure, and ensuring safety. The study emphasizes the necessity of addressing these barriers to enable widespread adoption. Green hydrogen offers numerous environmental benefits, such as storing surplus renewable energy, acting as a zero-emission fuel, and significantly mitigating greenhouse gas emissions. Its application in hard-to-abate industries, like steel and cement manufacturing, further highlights its role in supporting global sustainability goals. This review also underscores the importance of collaborative efforts among governments, industries, and researchers to advance green hydrogen technologies. By fostering innovation and public acceptance, green hydrogen can accelerate the energy transition and contribute to long-term climate resilience. This work provides actionable insights to promote the adoption of green hydrogen, showcasing its potential to reshape energy systems and support a low-carbon economy.